PH-dependent two Cd(II) coordination architectures with methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate and 1, 3-bis(4-pyridyl)propane mixed ligands: syntheses, crystal structures, and photoluminescent properties. (3rd May 2020) - Xue, Li-Ping; Zhang, Ying-Ge
ABSTRACT: Two new Sulfur-containing cadmium(II) coordination polymers {[Cd(HL)2 ](bpp)}n (1 ) and {[Cd(L)(bpp)(H2 O)]}n (2 ) (H2 L = methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate, and bpp = 1, 3-bis(4-pyridyl)propane) have been synthesized under different pH conditions and structurally characterized by the single-crystal X-ray diffraction and other physicochemical techniques. Structural analyses reveal that compound 1 exhibits a 1D double chain structure based upon dimeric [Cd2 (COO)2 ] subunit. Compound 2 features a 3D network which can be rationalized as a 3-fold 4-connected dia net. It is shown that the pH plays a crucial role in the formation of the resulting structures. Furthermore, solid photoluminescent properties of the two compounds make them potentially useful photoactive materials. GRAPHICAL ABSTRACT: